(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
This article analyzes the study of the history of Surkhandarya in the 30s of the XX century, as a historical source. In those years, the attention paid to industry by the Soviet government was not good. However, factory managers were often blamed for poor management of the cotton mills. One of the most important factors in the development of agriculture was a topical issue not only in the oasis but throughout the country